2010
DOI: 10.1016/s0034-7094(10)70064-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the Adequate Use of Statistical Tests of Hypothesis in Original Articles Published in the Revista Brasileira de Anestesiologia between January 2008 and December 2009

Abstract: The frequency of inadequate use of statistical tests in the articles published by the Revista Brasileira de Anestesiologia between January 2008 and December 2009 was 56.42%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This finding suggests an interaction between the responses of the HPA axis and the ANS to stress although the responses show opposite dynamics (higher cortisol vs. lower sAA). A higher concentration of cortisol may induce alterations in the sensitivity to catecholamines in rats [ 77 79 ]. Thus, long-term exposure to life stress may result in a lower reactivity of the ANS; however, this possibly is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests an interaction between the responses of the HPA axis and the ANS to stress although the responses show opposite dynamics (higher cortisol vs. lower sAA). A higher concentration of cortisol may induce alterations in the sensitivity to catecholamines in rats [ 77 79 ]. Thus, long-term exposure to life stress may result in a lower reactivity of the ANS; however, this possibly is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…for men); Agility dynamic test – time to complete tasks involving repeatedly standing from a chair, walking around cones, and returning to the chair; and cardiovascular endurance represented the time to complete an 880-yard walk. The AAHPERD battery test was completely described previously [22,23]. The GFFI was calculated using the sum of the percentile score of each test as described previously [22].…”
Section: Methodsmentioning
confidence: 99%
“…The AAHPERD battery test was completely described previously [22,23]. The GFFI was calculated using the sum of the percentile score of each test as described previously [22]. All items included in the AAHPERD Battery Test have demonstrated good reliability and validity for use in this age group.…”
Section: Methodsmentioning
confidence: 99%
“…Corroborating these findings, Pedrosa, Tirapegui, Rogero, et al [28], when comparing sedentary and trained animals, both with and without feed restriction (25 and 50% of ad libitum intake), observed higher muscle and liver glycogen values in the animals in the restricted groups. In addition, Wetter, Gazdag, Dean, et al [29] observed similar or higher muscle glycogen values in rats subjected to feed restriction (60% of consumed by the ad libitum group), as has been demonstrated by other studies [30,31].…”
Section: Discussionmentioning
confidence: 69%